SUBJECTIVE INFORMATION ESTIMATION TECHNIQUE FOR DETERMINATION OF PATIENT'S ORGANISM CONDITION USING THE HIERARCHY ANALYSIS METHOD - Vysotskaya, E. V.; Dovnar, A. I.; Porvan, A. P. (Radio Electronics, Computer Science, Control, 2010)
The authors consider the approach to estimation of experts’ opinion consistency when determining the patient’s organism condition. The hierarchy analysis method has been chosen to determine a degree of experts’ opinion consistency. The method permits to show relation between patient’s diseases and his organism general condition and to describe experts’ verdicts accurately.